Didactic Unit To Enhance Speaking Skill By Using Verb To Be Into A Flipped Classroom Approach (2018)
This document reports information related to a process of design and application of didactic material done to seventh grade students of a private institution in the city of Bogota. That material is a didactic unit focused on the speaking skill and was structured under the principles established by Jolly & Bolitho (2011) in terms of teaching materials development. Consequently, four stages were taken into account to develop the didactic unit: Identification of a need or problem, Exploration of the need or problem, Contextual Realization, Pedagogical realization and Physical production of the material.